Atomoxetine and citalopram alter brain network organization in Parkinson's disease. Issue 1 (6th September 2019) - Borchert, Robin J; Rittman, Timothy; Rae, Charlotte L; Passamonti, Luca; Jones, Simon P; Vatansever, Deniz; Vázquez Rodríguez, Patricia; Ye, Zheng; Nombela, Cristina; Hughes, Laura E; Robbins, Trevor W; Rowe, James B
Abstract: Parkinson's disease has multiple detrimental effects on motor and cognitive systems in the brain. In contrast to motor deficits, cognitive impairments in Parkinson's disease are usually not ameliorated, and can even be worsened, by dopaminergic treatments. Recent evidence has shown potential benefits from restoring other neurotransmitter deficits, including noradrenergic and serotonergic transmission. Here, we study global and regional brain network organization using task-free imaging (also known as resting-state), which minimizes performance confounds and the bias towards predetermined networks. Thirty-three patients with idiopathic Parkinson's disease were studied three times in a double-blinded, placebo-controlled counter-balanced crossover design, following placebo, 40 mg oral atomoxetine (selective noradrenaline reuptake inhibitor) or 30 mg oral citalopram (selective serotonin reuptake inhibitor). Neuropsychological assessments were performed outside the scanner. Seventy-six controls were scanned without medication to provide normative data for comparison to the patient cohort. Graph theoretical analysis of task-free brain connectivity, with a random 500-node parcellation, was used to measure the effect of disease in placebo-treated state (versus unmedicated controls) and pharmacological intervention (drug versus placebo). Relative to controls, patients on placebo had executive impairments (reduced fluency and inhibitory control), which was reflected in dysfunctional network dynamics in terms of reduced clustering coefficient, hub degree and hub centrality. In patients, atomoxetine improved fluency in proportion to plasma concentration ( P = 0.006, r 2 = 0.24), and improved response inhibition in proportion to increased hub Eigen centrality ( P = 0.044, r 2 = 0.14). Citalopram did not improve fluency or inhibitory control, but its influence on network integration and efficiency depended on disease severity: clustering ( P = 0.01, r 2 = 0.22), modularity ( P = 0.043, r 2 = 0.14) and path length ( P = 0.006, r 2 = 0.25) increased in patients with milder forms of Parkinson's disease, but decreased in patients with more advanced disease (Unified Parkinson's Disease Rating Scale motor subscale part III > 30). This study supports the use of task-free imaging of brain networks in translational pharmacology of neurodegenerative disorders. We propose that hub connectivity contributes to cognitive performance in Parkinson's disease, and that noradrenergic treatment strategies can partially restore the neural systems supporting executive function. Abstract : Targeting the deficits in serotonergic and noradrenergic transmission can restore cognitive function in Parkinson's disease. Borchert et al. use resting-state imaging to show that changes in hub connectivity on atomoxetine correlate with improved response inhibition while the potential therapeutic effect of citalopram depends on severity of disease. Graphical Abstract: